Activities of Daily Living in Children With Developmental Coordination Disorder: Performance, Learning, and Participation. Issue 11 (1st November 2015) - Van der Linde, Berdien W.; van Netten, Jaap J.; Otten, Bert; Postema, Klaas; Geuze, Reint H.; Schoemaker, Marina M.
Abstract : Background: Children with developmental coordination disorder (DCD) face evident motor difficulties in daily functioning. Little is known, however, about their difficulties in specific activities of daily living (ADL). Objective: The purposes of this study were: (1) to investigate differences between children with DCD and their peers with typical development for ADL performance, learning, and participation, and (2) to explore the predictive values of these aspects. Design: This was a cross-sectional study. Methods: In both a clinical sample of children diagnosed with DCD (n=25 [21 male, 4 female], age range=5–8 years) and a group of peers with typical development (25 matched controls), the children's parents completed the DCDDaily-Q. Differences in scores between the groups were investigated using t tests for performance and participation and Pearson chi-square analysis for learning. Multiple regression analyses were performed to explore the predictive values of performance, learning, and participation. Results: Compared with their peers, children with DCD showed poor performance of ADL and less frequent participation in some ADL. Children with DCD demonstrated heterogeneous patterns of performance (poor in 10%–80% of the items) and learning (delayed in 0%–100% of the items). In the DCD group, delays in learning of ADL were a predictor for poor performance of ADL, and poor performance of ADL was a predictor for less frequent participation in ADL compared with the control group. Limitations: A limited number of children with DCD were addressed in this study. Conclusions: This study highlights the impact of DCD on children's daily lives and the need for tailored intervention.